2022
DOI: 10.1002/da.23243
|View full text |Cite
|
Sign up to set email alerts
|

Distinct stress‐related medial prefrontal cortex activation in women with depression with and without childhood maltreatment

Abstract: Background Emerging evidence has highlighted the moderating effect of childhood maltreatment (CM) in shaping neurobiological abnormalities in major depressive disorder (MDD). However, whether neural mechanisms underlying stress sensitivity in MDD are affected by the history of CM is unclear. Methods Two hundred and thirteen medication‐free female participants were recruited for a functional magnetic resonance imaging study assessing the effects of psychosocial stress on neural responses. The Montreal Imaging S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 50 publications
1
9
0
2
Order By: Relevance
“…Sensitivity analyses were used to test whether the primary findings (fibre length of the PCR-R, ACR-R, and ATR) would be affected by different types of CM (i.e. sexual, physical, and emotional abuse, physical and emotional neglect) (Dong et al, 2022 ). Besides, previous studies proposed that different dimensions of CM (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensitivity analyses were used to test whether the primary findings (fibre length of the PCR-R, ACR-R, and ATR) would be affected by different types of CM (i.e. sexual, physical, and emotional abuse, physical and emotional neglect) (Dong et al, 2022 ). Besides, previous studies proposed that different dimensions of CM (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Threats involve varying degrees of physical and sexual abuse, witnessing domestic violence, and so on, while deprivation involves various forms of neglect (McLaughlin et al, 2019 ). Thus threat dimension included sexual, physical, or emotional abuse, and the deprivation dimension included physical or emotional neglect (Dong et al, 2022 ). The sensitivity analysis results showed that the fibre length of PCR-R and ACR-R was significantly shorter ( p < .05) in the CM group than in the non-CM group in most types of trauma.…”
Section: Resultsmentioning
confidence: 99%
“…53 MDD-by-CM interaction has been reported in PFC under stress conditions. 11,54 The FC abnormality in PFC could distinguish MDDCM from MDDNCM. 55 In line with previous literature, the FCs of OFC-dlPFC and OFC-vmPFC were higher in HCCM or MDDNCM, and were positively correlated with CTQ scores and HAMD-c.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 A recent study has reported a CM Â MDD diagnosis interactive effect on stress-related neural activation located in the medial prefrontal cortex (mPFC). 11 Overlapping effects of MDD and CM on amygdala functional connectivity (FC) in the prefrontal and limbic systems were reported in previous research. 12 The longitudinal CM-related increases in functional connectivity (FC) between default mode network, dorsal attention network, and frontoparietal systems were thought to mediate the relationship between CM experience and depressive symptoms in MDD patients.…”
mentioning
confidence: 85%
See 1 more Smart Citation